Conditioning status of the first XFEL gun at pitz - I. Isaev (2018)
The paper describes the recent results of conditioning and dark current measurements for the photocathode RF gun at the photoinjector test facility at DESY, Zeuthen site (PITZ). The aim of PITZ is to develop and operate an optimized photo injector for free electron lasers and linear accelerators which require high quality beams. In order to get high gradients in the RF gun extensive conditioning is required. A data analysis of the conditioning process is based on data saved by a Data Acquisition system (DAQ). Conditioning results of the first gun cavity for the XFEL is presented. The events which occurred during the conditioning are briefly described. Copyright © 2013 CC-BY-3.0 and by the respective authors.